Reality of Creative Education and Problems with Education Management in Vietnam: A Case Study of Some Northern Provinces - Hang, Do Thi Thu; Minh, Trinh Van (VNU Journal of Science: Education Research; Vol 35 No 4DO - 10.25073/2588-1159/vnuer.4307, 2019)
Creative education, the activity that helps learners nurture creative spirit, ideas and capacity, is the "main way" to form creative people and thereby promotes the development of society, making it a creative one. The search for creative education in Vietnam is an issue that needs to be studied and evaluated in order to make recommendations on educational management in high schools. This article focuses on creative education and management issues in schools; analyzes and assesses the current status of creative education in Vietnam high schools in Hanoi, Nam Dinh and Quang Ninh through a survey for 190 teachers and 220 students from three high schools about factors that form creative education, the level of expression and relationship between the components of creative education as well as factors that impede creative education development in high schools; thereby making recommendations on educational management in Vietnam today.